Viewing Profile: PJS
PJS
Awakening
Member Group: Basic Member
Joined: Aug 17, 2006 





Signature 
x^2 + 1 = 0
x^3  2x^2 = 1 2x^2 = (i^2/x^2)  x^3 2 = (i^2/x^2/x^2)  (x^3/x^2) 1 = (i^2/2)  (x/2) 1 = 0.5  0.5 x/2 = 0.5 x = 1 this is a contradiction from x^3 = 1, x^3/x^2 = 1/1 = x = 1, if x = 1 then x^3 equals 1 as well. However the equation shows that x^3 = 1. x therefore becomes 1 and 1 at the same time proving that x^2 = 1 is a mathematical error. 
LoFi Version  Time is now: 23rd May 2018  11:38 PM 